Growth After Adenotonsillectomy for Obstructive Sleep Apnea: An RCT - Eliot S. Katz; Reneé H. Moore; Carol L. Rosen; Ron B. Mitchell; Raouf Amin; Raanan Arens; Hiren Muzumdar; Ronald D. Chervin; Carole L. Marcus; Shalini Paruthi; Paul Willging; Susan Redline (2014)
Adenotonsillectomy for obstructive sleep apnea syndrome (OSAS) may lead to weight gain, which can have deleterious health effects when leading to obesity. However, previous data have been from nonrandomized uncontrolled studies, limiting inferences. This study examined the anthropometric changes over a 7-month interval in a randomized controlled trial of adenotonsillectomy for OSAS, the Childhood Adenotonsillectomy Trial.A total of 464 children who had OSAS (average apnea/hypopnea index [AHI] 5.1/hour), aged 5 to 9.9 years, were randomized to Early Adenotonsillectomy (eAT) or Watchful Waiting and Supportive Care (WWSC). Polysomnography and anthropometry were performed at baseline and 7-month follow-up. Multivariable regression modeling was used to predict the change in weight and growth indices.Interval increases in the BMI z score (0.13 vs. 0.31) was observed in both the WWSC and eAT intervention arms, respectively, but were greater with eAT (P < .0001). Statistical modeling showed that BMI z score increased significantly more in association with eAT after considering the influences of baseline weight and AHI. A greater proportion of overweight children randomized to eAT compared with WWSC developed obesity over the 7-month interval (52% vs. 21%; P < .05). Race, gender, and follow-up AHI were not significantly associated with BMI z score change.eAT for OSAS in children results in clinically significant greater than expected weight gain, even in children overweight at baseline. The increase in adiposity in overweight children places them at further risk for OSAS and the adverse consequences of obesity. Monitoring weight, nutritional counseling, and encouragement of physical activity should be considered after eAT for OSAS.